Employer Branding Dimensions and Organizational Information Availability on LinkedIn as Determinants of Generation Z’s Intention to Apply in Jakarta and Tangerang - Irvan Irvan; Wanda Gema Prasadio Akbar Hidayat; Rajesh Prettypal Singh (Dinasti International Journal of Digital Business Management, 2026)
This study aims to analyze the influence of employer branding dimensions (interest value, social value, economic value, development value, and application value) and the availability of organizational information on LinkedIn on Generation Z’s intention to apply in Jakarta and Tangerang. Generation Z is expected to dominate Indonesia’s future workforce; therefore, understanding the factors that influence their intention to apply for jobs is essential for organizations. This research employs a quantitative method with a conclusive research design using a descriptive research approach and a single cross-sectional design. Data were collected through an online questionnaire from 178 Generation Z respondents who reside in Jakarta and Tangerang, actively use LinkedIn, and are currently seeking employment. The sampling technique used was non-probability sampling with a judgmental sampling approach. The data were analyzed using IBM SPSS Statistics 27 through validity testing, reliability testing, classical assumption tests, and multiple linear regression analysis. The findings reveal that interest value and economic value have a positive influence on intention to apply, with interest value showing the strongest effect. Meanwhile, social value, development value, application value, and the availability of organizational information on LinkedIn do not significantly influence intention to apply. This study provides practical implications for organizations to prioritize innovation, job variety, and compensation transparency in their employer branding strategies to more effectively attract Generation Z talent.